Classification of the cyclone types over the South Atlantic Ocean in projections with RegCM4 and GCMs - Marrafon, Vitor Hugo; Reboita, Michelle Simões; da Rocha, Rosmeri Porfírio; de Jesus, Eduardo Marcos (Revista Brasileira de Climatologia, 2022)
This study aims to classify the types of cyclones in the South Atlantic Ocean in three projections of the Regional Climate Model (RegCM4), as well as of the global models (GCMs) that provide the boundary conditions for the regional, and to identify systems that transition to tropical (TT). The climatic scenario used is RCP8.5. Classification of cyclone types uses three algorithms: the first to identify and track cyclones in the South Atlantic Ocean based on relative vorticity at 925 hPa; the second to provide thermal characteristics of cyclones through the Cyclone Phase Space methodology and the third to separate cyclones based on their thermal characteristics. Considering the period 2020-2050 (2051-2080), the GCMs and RegCM4 ensembles project a slight reduction (increase) in the frequency of tropical cyclones when compared to the present climate (1979-2005). For extratropical cyclones, there is a negative trend in their frequency. One of the initial hypotheses of this study was that in a warming scenario, there would be an increase in the number of TT, however the results obtained do not indicate a change in their frequency since in present and future climates the number of transitions is ~ 2.8 systems per decade in both ensemble. Este estudio tiene como objetivo clasificar los tipos de ciclones sobre el Océano Atlántico Sur en tres proyecciones del Modelo Climático Regional (RegCM4), así como en los modelos globales (GCM) que proporcionaron las condiciones de contorno para el regional, e identificar sistemas que transición a tropical (TT). El escenario climático utilizado es RCP8.5. La clasificación de los tipos de ciclones implica el uso de tres algoritmos: el primero para identificar y rastrear ciclones en el Océano Atlántico Sur en función de la vorticidad relativa a 925 hPa; el segundo para proporcionar las características térmicas de los ciclones a través de la metodología Cyclone Phase Space y el tercero para separar los ciclones en función de sus características térmicas. Considerando el período ...